INTERNALIZATION OF THE VALUES OF RASAI CULTURAL WISDOM IN KNITTING THE ATTITUDE OF TOLERANCE AMONG SOCIAL GROUPS (A Naturalistic Study on Tabanga Community in Ternate City) - Muhammad, Syahril; Hassim, Rustam (Universitas Hasanuddin, 2020)
The internalization of the values of Rasai cultural wisdoms by Tabanga community in Ternate City is an effort to instil a sense of brotherhood towards others. This Rasai culture has been built not relying on the same blood, culture and religion. Rather, it relies on the recognition, appreciation, and mutual agreement among parties. This is an effort to minimize and avoid negative impacts of intolerant attitudes among social groups. This study focuses on the assimilation and adaptation processes among social groups with multicultural basis which characterize the people of Ternate. This study aims at analyzing the assimilation and adaptation processes among social groups through the internalization of the values of Rasai cultural wisdoms in Tabanga community in Ternate City; analyzing the inhibiting factors of the internalization of the values of Rasai culturaln wisdoms in knitting the tolerance attitudes among social groups; and analyzing the impacts of Rasai culture of Tabanga community in Ternate City. This study applied ethnographic approach. The results of the study show that the assimilation and adaptation processes among social groups through the internalization of the values of Rasai cultural wisdoms in Tabanga community in Ternate City are able to knit the tolerance attitudes among social groups. This is evident in the embodiment of mutual cooperation attitudes and collaboration among social groups either among religious groups or among ethnic groups in Tabanga community of Ternate City. The inhibiting factors of the internalization of the values of Rasai cultural wisdoms in knitting the tolerance attitudes among social groups include the dominance of kinship, the low level of education achievement of the community, and not yet built a model of multicultural society-based attitude building in Tabanga community of Ternate City. The attitude of openness of Ternate community in responding the existence of Rasai culture is so strong. In addition, such culture is one of the instruments to strongly develop a peaceful civilizationof the future of North Maluku.